Antero-Posterior Relationship of Maxillary Central Incisors to The Forehead in Jharkhand Population - Sharma, Shreya; Sunil, M.K; Kumari, Archana; Sharma, Kanchan; Yasmin, Yeptasam; Burela, Jugal (Journal of Neonatal Surgery, 2025)
Background: Facial aesthetics play a crucial role in an individual’s social, professional, and personal life, making orthodontic treatment a popular choice for enhancing facial appearance. The maxillary central incisors significantly contribute to smile aesthetics, and their anteroposterior (AP) positioning relative to facial landmarks is a critical aspect of orthodontic diagnosis and treatment planning. This study evaluates the AP location of maxillary central incisors in adult African females relative to the forehead, assessing its reliability as a reference marker. Methods: A total of 100 participants (50 cases and 50 controls) were analyzed using digital imaging. The AP location of the maxillary mid-incisors relative to the forehead and forehead angulation was determined using a metric ruler and protractor. The correlation between the maxillary central incisors and the forehead was assessed using statistical analysis. Results: In the study group, 68% of subjects had their maxillary central incisors positioned ahead of the glabella, while 26% had them positioned between the forehead facial axis (FFA) point and the glabella. In contrast, in the control group, only 26% had their incisors ahead of the glabella, while 46% had them between the FFA point and glabella. The forehead angulation was significantly different between the study and control groups (p = 0.00), and the AP location of the maxillary incisors relative to the forehead FFA point varied significantly (p = 0.001). The regression analysis showed a strong correlation between the maxillary mid-incisors' AP position and the forehead (r² = 0.310 in the control group), but a weaker correlation with forehead angulation (r² = 0.185 in the study group). Conclusion: The study confirms that the maxillary central incisors' AP positioning is significantly associated with the forehead, making it a reliable reference point for orthodontic evaluation in adult females. However, the correlation between incisor position and forehead angulation is weak. The study also found that females in the research model had a more rounded forehead, while males exhibited a flatter forehead. Considering the forehead as a reference marker can aid in treatment planning, and for Indian patients, achieving a harmonious AP relationship between the maxillary incisors and the forehead should be a therapeutic objective to enhance facial balance and aesthetics